Analysis of an Efficient Routing Protocol for Mobile AD-HOC Networks - Altaf, C; Ahmed, Shah Aqueel (2021 International Conference on Innovative Computing, Intelligent Communication and Smart Electrical Systems (ICSES), 2021)
Power and line saving in ad hoc mobile networks are important (MANET). Not only the transmission ratio but also network life is affected by these two factors. In this paper, we provided an efficient and easy routings agreement to extend the service life and dispense as fairly as possible the traffic of the networks. In addition, a service capacity concept is implemented to reverse the congestion move around a point. The mentioned routings protocols are thus able to prevent associate congestion and reach a higher packets transmission rate. A routings design is the main factorsand should be carefully addressed to achieve efficient and solid communication between UAVs. This subject has drown attention many scholars and different routings protocol have been put advance for improving data transmission efficiency in FANETs due to its significance and usefulness. In this paper we are therefore conducting a report on the astate of the art routings protocol in the last few year ago. Firstly, a detailed analysis of the FANETs routing has recently been carried out by differentiating them completely according to their routing process. Then we analyze the characteristics and the service quality metrics of each protocol against each other. Finally, we suggest a few unresolved problems and possible FANET routing research directions